The effects of microwave radiation on microbial cultures - Janković Slobodan M.; Milošev Milorad Z.; Novaković Milan Lj (Srpsko lekarsko drustvo, 2014)
Microwaves are non-ionizing electromagnetic waves with frequencies between 0.3 and 300 GHz. Both humans and microorganisms living on the human body are exposed to significant doses of microwave radiation in everyday life. Whether and how microwave radiation could influence the viability and growth of microorganisms is the subject of this educational paper. Studies on the effects of microwaves on the growth of microbial cultures were searched for in biomedical journals indexed in MEDLINE from 1966 to 2012. The published studies showed that microwaves produce significant effects on the growth of microbial cultures, which vary from the killing of microorganisms to enhancement of their growth. The nature and extent of the effect depend on the frequency of microwaves and the total energy absorbed by the microorganisms. Low energy, low frequency microwaves enhance the growth of microorganisms, whereas high energy, high frequency microwaves destroy the microorganisms. However, neither the effects of a wide spectrum of frequencies nor the effects of a wide range of absorbed energies have been investigated. Considering the potentially deleterious influence of microwaves on the symbiotic balance between microorganisms and the human host, further research on the effects of the complete frequency and energy spectra of microwave radiation on the growth of microorganisms is necessary.